Carotid sinus hypersensitivity in patients presenting with syncope. Issue 5 (November 1979) - Davies, A B; Stephens, M R; Davies, A G
Abstract : In 23 patients (ages 44 to 81) presenting with syncope, vertigo, or transient amnesia, carotid sinus massage produced a significant bradycardia in association with symptoms. The 10 most severely symptomatic patients were studied electrophysiologically, including measurement of intracardiac conduction times and corrected sinus node recovery times, as well as with carotid sinus massage before and after atropine. The only detectable abnormality in five of this group was asystole produced by carotid sinus massage; the other five had, in addition, evidence of either sinuatrial disease or an intracardiac conduction defect. Cardiac pacing in these 10 patients completely abolished their symptoms. In a control group of 52 asymptomatic patients (ages 36 to 87), an abnormal response to carotid sinus massage was uncommon (2%).